Permainan Kartu Lambang Bilangan: Upaya Meningkatkan Kemampuan Berhitung Pada Anak Usia Dini - Setyawan, Dedi; Dzulkifli, Dzulkifli; Dwi Arumsari, Andini (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2024)
Early childhood experiences delays in calculating basic numbers. Basic numbers are an important part in supporting early childhood to enter the next level of education. Early childhood is the right time to stimulate various developments and potentials possessed by children. This study aims to analyze the numeracy skills of early childhood through Number Symbol Cards. This study uses an experimental research type. This study was conducted at PAUD Tunas Bangsa located in Kel. Ploso - Kec. Tambaksari, Surabaya. The subjects in this study were 17 students. The subjects at PAUD Tunas Bangsa were 3-5 years old. The analysis test was carried out using pretest and posttest data, and analyzed using a paired sample t-test. The results of the study found that the sig result was 0.000, so there was a difference in the numeracy skills of early childhood before and after being given Number Symbol Cards. Therefore, number symbol cards have an important role in improving the numeracy skills of early childhood. The findings of this study contribute to early childhood education as an alternative in improving the numeracy skills of early childhood by using number cards. So that it can prepare for further education better.